Stochasticity of the magnetic field lines and high Z ion motion - Shishkin, O.A.; Shishkin, A.A.; Wobig, H. (Вопросы атомной науки и техники, 2000)
Stochastic layer of the magnetic field lines is numerically analyzed for the realistic magnetic field of HELIAS reactor with use of the flux coordinate system. Analytical expressions for the stochastic diffusion coefficients are obtained for the simplified magnetic field model.